A neuralization-promoting electrospinning fiber membrane and preparation method thereof
By self-assembling 3,5-DHBA with Zn2+ to form Zn-MOF particles and loading it into electrospinned fiber membranes, the clinical application instability of 3,5-DHBA in the field of nerve regeneration is solved, its stability and biological activity are improved in the environment of high oxidative stress, and neurovascular coupling regeneration and healing of diabetic wounds is promoted.
Patent Information
- Application Number
- CN202411729875.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2044-11-29
AI Technical Summary
3,5-DHBA is unstable in the field of nerve regeneration, and is prone to oxidation, resulting in limited antioxidant performance, affecting its biological activity and durability.
Zn-MOF particles are formed by self-assemblying 3,5-DHBA with Zn2+ and loading these particles into an electrospinned fiber membrane to form a proneurogenic electrospinned fiber membrane, protecting 3,5-DHBA from oxidation.
It effectively protects the biological activity and durability of 3,5-DHBA, significantly improves its stability and clinical application value in a high oxidative stress environment, and promotes neurovascular coupling regeneration and healing of diabetic wounds.
Smart Images

Figure CN119185622B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of electrospinning fiber membranes, in particular to a neuralization-promoting electrospinning fiber membrane and a preparation method thereof. Background Art
[0002] The reasons for delayed healing of diabetic wounds are complex and diverse, including excessive inflammatory response, oxidative stress, peripheral nerve damage and vascular reduction, bacterial infection, and zinc deficiency, among which oxidative stress, peripheral nerve damage and vascular reduction are the main factors.
[0003] In diabetic patients, the long-term hyperglycemic microenvironment leads to the production of a large amount of reactive oxygen species (ROS) and inflammatory mediators, which cause endothelial cell dysfunction and neuronal damage, inhibit cell proliferation and migration, and also cause insufficient endothelial cell tube formation. This affects the delivery of oxygen and nutrients to the wound area, aggravates the ischemia and hypoxia of peripheral nerves, and further hinders the repair of diabetic wounds. As diabetes progresses, at least 50% of diabetic patients will develop diabetic neuropathy. To make matters worse, due to hyperglycemia and microvascular complications, peripheral nerve repair becomes difficult in diabetic patients, resulting in segmental axonal demyelination and slow nerve growth. This makes it impossible for nerve fibers to keenly sense environmental changes and transmit signals, thereby hindering the biological activities that regulate wound epithelial regeneration.
[0004] Studies have shown that nerve regeneration usually precedes vascular reconstruction and promotes the formation of new blood vessels by regulating the secretion of neurotransmitters and growth factors. The bidirectional interaction between nerves and blood vessels plays an important role in skin wound repair. Although a variety of multifunctional dressings suitable for wounds have been developed, there are still few reports on dressings that promote neurovascular coupling regeneration. Therefore, promoting neurovascular coupling in wounds as a breakthrough in the effective treatment of diabetic wounds deserves attention.
[0005] 3,5-Dihydroxybenzoic acid (3,5-DHBA) has been proven to effectively promote the repair of damaged nerves by regulating the cell cycle, energy metabolism and neuronal differentiation of neural progenitor cells, showing unique neurogenicity. As a specific lactate receptor (HCAR1) agonist, it can also enhance the effects of HCAR1 and its ligands in the brain, and promote the expression of vascular endothelial growth factor A (VEGFA) and angiogenesis by upregulating the phosphorylation of ERK1 / 2 and Akt. Therefore, it may have good application prospects in promoting the regeneration of neurovascular coupling in diabetic wounds.
[0006] However, as a flavonoid compound, the antioxidant effect of 3,5-DHBA depends on its phenolic part, which is unstable and easily oxidized. In the high oxidative stress environment of diabetes, 3,5-DHBA easily reacts with reactive oxygen species (ROS), so its antioxidant properties are severely limited. This oxidative sensitivity not only limits the biological activity and persistence of 3,5-DHBA in the body, but also significantly increases its instability during formulation development and storage. Therefore, although 3,5-DHBA shows good therapeutic prospects in the field of nerve regeneration, its clinical application still needs to overcome the problem of oxidative stability. Summary of the invention
[0007] The purpose of the present invention is to solve the instability of clinical application of 3,5-DHBA in the field of nerve regeneration, and to provide a neuralization-promoting electrospun fiber membrane loaded with 3,5-DHBA / Zn-MOF particles and a preparation method thereof. Through the rigid structure of the particles, 3,5-DHBA can be effectively protected from oxidation and inactivation, thereby overcoming its natural defects as a phenol compound.
[0008] The neuralization-promoting electrospun fiber membrane of the present invention comprises a plurality of nanofibers loaded with 3,5-DHBA / Zn-MOF particles, wherein the 3,5-DHBA / Zn-MOF particles are composed of Zn 2+ and 3,5-DHBA self-assembled to form the neuralization-promoting electrospun fiber membrane 2+ The mass percentage is 0.48-0.66%.
[0009] Preferably, the diameter of the nanofibers is 380-440 nm; the particle size of the 3,5-DHBA / Zn-MOF particles is 100-200 nm, and the crystallinity is 55.6%-64.0%.
[0010] The present invention provides a method for preparing a neuralization-promoting electrospun fiber membrane, the method comprising the following steps:
[0011] Step (1): Preparation of Zn 2+ An electrospinning solution having a concentration of 0.44-1.32 mg / mL, and electrospinning the electrospinning solution to obtain a nanofiber membrane;
[0012] Step (2): immerse the nanofiber membrane obtained in step (1) in a 3,5-DHBA ligand solution, take it out after self-assembly reaction for 0.5-2 hours, and dry it to obtain the neuralization-promoting electrospun fiber membrane (PGZ electrospun membrane), wherein the nanofibers in the PGZ electrospun membrane present a three-dimensional network structure.
[0013] Preferably, the electrospinning solution in step (1) further comprises a biocompatible hydrophilic polymer, wherein the biocompatible polymer is selected from any one or a combination of at least two of polycaprolactone, lactide-caprolactone copolymer, sodium alginate, chitosan, gelatin or hyaluronic acid; and the electrospinning solution in step (1) further comprises a water-soluble solvent.
[0014] Preferably, the electrospinning solution in step (1) is a gelatin / polycaprolactone electrospinning solution, and the nanofiber membrane is a gelatin / polycaprolactone nanofiber membrane.
[0015] Preferably, the molar concentration of 3,5-DHBA in the 3,5-DHBA ligand solution in step (2) is not less than one-fourth of the molar concentration of Zn in the electrospinning solution in step (1). 2+ The molar concentration of .
[0016] Preferably, the mass volume percentage concentration of the 3,5-DHBA ligand solution is 4%.
[0017] Specifically, the electrospinning solution in step (1) is prepared by mixing a polycaprolactone solution and a gelatin aqueous solution.
[0018] Specifically, step (1) comprises: using trifluoroethanol as a solvent to prepare a polycaprolactone solution with a mass volume percentage concentration of 10%; then adding zinc nitrate hexahydrate and stirring evenly to obtain a polycaprolactone / zinc nitrate solution, wherein the concentration of zinc nitrate hexahydrate in the polycaprolactone / zinc nitrate solution is 4-12 mg / mL; then, mixing an aqueous gelatin solution with a mass volume percentage concentration of 20% with the polycaprolactone / zinc nitrate solution in equal volumes to obtain a gelatin / polycaprolactone electrospinning solution, wherein the Zn in the gelatin / polycaprolactone electrospinning solution is 4-12 mg / mL. 2+ The concentration is 0.44-1.32 mg / mL; the gelatin / polycaprolactone electrospinning solution is subjected to electrospinning to obtain a gelatin / polycaprolactone nanofiber membrane.
[0019] Preferably, the drying parameters in step (2) are a drying temperature of 37° C. and a drying time of 3 h.
[0020] Specifically, the self-assembly reaction time of step (2) is preferably 0.5-1 h.
[0021] Preferably, the electrospinning parameters are: loading voltage 15-20 kV high voltage, injection speed 0.2-1.0 mL / h, distance between collector and needle tip 100-120 mm, collector rotation speed 100-200 rpm.
[0022] Preferably, the Zn in step (1) 2+ Derived from any one of zinc nitrate hexahydrate, zinc acetate, and zinc chloride.
[0023] The invention provides an application of a neuralization-promoting electrospun fiber membrane in a dressing material, wherein Zn 2+ The mass percentage is 0.48-0.66%, and the neuralization-promoting electrospun fiber membrane is prepared by the above preparation method.
[0024] The beneficial effects of the present invention are as follows: the polycaprolactone (PCL) / gelatin (GEL) electrospun fiber membrane containing 3,5-DHBA / Zn-MOF particles prepared by the present invention can not only remove ROS, but also promote the coordinated regeneration of blood vessels and nerves, accelerate the repair of diabetic wounds, and the preparation method is simple and easy, and the raw materials are affordable and readily available;
[0025] PGZ electrospun membrane loaded with Zn 2+ The PGZ electrospun membrane is electrostatically coordinated with 3,5-DHBA to automatically assemble into a crystal polymer with a special structure. The physical, chemical and biological properties of the obtained PGZ electrospun membrane meet the characteristics of wound dressings.
[0026] Advantages of PGZ electrospun membrane in drug release characteristics: released Zn 2+ Compared with 3,5-DHBA, it is relatively slow and long-lasting, which not only avoids the biological toxicity caused by the initial explosive release, but also protects the biological activity and persistence of 3,5-DHBA in the body, and effectively improves the clinical application stability of 3,5-DHBA under high oxidative stress environment;
[0027] The crystallinity of 3,5-DHBA / Zn-MOF particles determines the number of uncoordinated carboxyl and phenolic hydroxyl groups remaining on the surface of PGZ electrospun membranes, which can be controlled by adjusting the Zn content in the electrospinning solution. 2+ The concentration controls the crystallinity and adjusts the coagulation performance of the PGZ electrospun membrane to suit different application areas;
[0028] The results of in vitro experiments showed that PGZ electrospun membrane can not only promote the growth and migration of neurons, endothelial cells and fibroblasts, and protect cells from oxidative stress under high sugar; it also has good antioxidant properties, plays a significant role in the repair of neurons, and promotes axon growth, angiogenesis and collagen deposition; the diabetic rat skin injury model further verified its good effect in promoting wound healing in diabetic rats; it provides new ideas for the field of neurovascular coupling repair of chronic diabetic wounds. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 The figure is a schematic diagram of the preparation process of the neuralization-promoting electrospun fiber membrane of the present invention.
[0030] Figure 2Representative scanning electron microscope (SEM) images of PGZ4 samples obtained by immersing in 3,5-DHBA ligand solution for 0.5, 1 and 2 h in 1.2 of Example 1.
[0031] Figure 3 These are representative images of the PGZ4 samples obtained after drying at 37°C for 1, 3, 6, 12 and 24 h in 1.2 of Example 1.
[0032] Figure 4 These are representative pictures of the PGZ4 samples obtained after drying at 37, 45 and 55° C. for 3 hours in 1.2 of Example 1.
[0033] Figure 5 This is the quantitative detection result of Schwann cell (SC) activity of the sample obtained in 1.1 of Example 1.
[0034] Figure 6 The representative scanning electron microscope (SEM) image and zinc (Zn) element energy dispersive X-ray spectroscopy (EDS) diagram of the experimental sample in Example 1.
[0035] Figure 7 7A and 7B show the X-ray diffraction pattern (XRD) and Fourier transform infrared spectrum (FTIR).
[0036] Figure 8 for Figure 7 The analysis results of A, Figure 8 A is the locally enlarged XRD pattern of the characteristic peak of MOF; Figure 8 B is the statistical data of MOF peak area of each group, Figure 8 C is the statistical data of the crystallinity of each group of MOF peaks.
[0037] Fig. 9 The in vitro degradation of the experimental samples in Example 3 and 3,5-DHBA / Zn 2+ Release result diagram, including the weight loss rate of each group of samples after soaking for different time ( Fig. 9 A) DHBA release ( Fig. 9 B) and Zn 2+ Release curve ( Fig. 9 C).
[0038] Fig.10 The results of the in vitro coagulation, swelling, hemolysis and antioxidant performance of the experimental samples in Example 4 are shown in Figure 4, including the relative hemostasis rate ( Fig.10 A) Swelling rate ( Fig.10 B) Hemolysis rate ( Fig.10 C) and 1,1-diphenyl-2-picrylhydrazyl (DPPH) scavenging rate ( Fig.10 D); electrospun membrane hemolysis ( Fig.10E) and antioxidant activity ( Fig.10 F) Representative images.
[0039] Fig.11 The results of the effects of different electrospun membranes on the biological behavior of Schwann cells (SC) in Example 6, including immunofluorescence staining images of Schwann cells (SC) morphology, proliferation, migration and reactive oxygen species (ROS) expression ( Fig.11 A); After incubation in the material extraction solution for 2 days, SC cell viability ( Fig.11 B) and the percentage of 5-ethynyl-2'-deoxyuridine (EdU)-positive cells ( Fig.11 C); The number of SCs that migrated in the extraction solutions of various materials ( Fig.11 D) and ROS fluorescence intensity ( Fig.11 E).
[0040] Fig.12 The results of the effects of different electrospun membranes on the biological behavior of PC12 cells in Example 6, including the cell morphology of PC12 cells cultured in different SCs conditioned medium ( Fig.12 A) Percentage of neurite cells ( Fig.12 B) Quantitative analysis results of neurite length ( Fig.12 C); RT-PCR analysis results of SYN, GAP-43 and TUJ-1 gene expressions among different groups ( Fig.12 D).
[0041] Fig.13 The cell activity results of Example 6 and Example 7 are shown in FIG. Fig.13 A is the cell activity of PC12 cells after incubation in the material extraction solution for 2 and 5 days in Example 6; Fig.13 B is the cell activity of vascular endothelial cells (VEC) after incubation in the material extraction solution for 1 and 3 days in Example 7; Fig.13 C is the cell activity of VEC after incubation in SC conditioned medium for 1 and 3 days in Example 7; Fig.13 D is the cell activity of RS1 cells after incubation in the material extraction solution for 1 and 3 days in Example 8; Fig.13 E is the cell activity of RS1 cells in Example 8 after incubation in SC conditioned medium for 1 and 3 days.
[0042] Fig.14 The statistical diagram of the effects of different electrospun membranes on the tube formation of vascular endothelial cells (VECs) in Example 7 includes ROS expression of VECs in the material extract, cell migration and tube formation images after 6 hours ( Fig.14 A), the number of vascular nodes after 6 hours ( Fig.14 C) and total branch length ( Fig.14D) Statistical analysis; ROS expression of VECs in SCs conditioned medium, cell migration and tube formation images after 6 hours ( Fig.14 B), the number of vascular nodes after 6 hours ( Fig.14 E) and branch length ( Fig.14 F) Statistical analysis results.
[0043] Fig.15 The images of the tubes formed by VECs in Example 7 after culturing in the material extract (PG and PGZ4 groups) and SC conditioned medium (PG-SCs and PGZ4-SCs) for 2 and 6 hours ( Fig.15 A); Number of vascular nodes ( Fig.15 B) and branch length ( Fig.15 C) Statistical results graph.
[0044] Fig.16 The evaluation results of different electrospun membranes on the biological behavior of skin fibroblasts (RS1 cells) in Example 8: ROS expression and cell migration images of RS1 cells in the material extract ( Fig.16 A) ROS fluorescence intensity ( Fig.16 B) Number of migrated RS1 cells ( Fig.16 C); ROS expression and cell migration images of RS1 cells in SC conditioned medium ( Fig.16 A) ROS fluorescence intensity ( Fig.16 D) and the number of migrated RS1 cells ( Fig.16 E).
[0045] Fig.17 The wound healing experiment results of diabetic rats in Example 9, including the establishment of a diabetic back wound model and a schematic diagram of the treatment process ( Fig.17 A); Representative images of wound areas after different treatments on days 0, 3, 7, and 14 ( Fig.17 B) and statistical results of healing area ( Fig.17 C).
[0046] Fig.18 The hematoxylin-eosin (H&E) staining images of wound tissues of diabetic rats in Example 9 on days 3, 7 and 14 ( Fig.18 A) and the statistical results of the number of inflammatory cells in wound tissue ( Fig.18 B).
[0047] Fig.19 Masson staining images of wound tissues of diabetic rats at days 3, 7 and 14 in Example 9 ( Fig.19 A) and quantitative results of collagen deposition ( Fig.19 B).
[0048] Fig. 20The immunohistochemical staining results of the diabetic wound tissue in Example 9, wherein Fig. 20 A is the staining image of neurogenesis markers (NGF and GAP43) on day 7. Fig. 20 C is the statistical result of NGF expression level, Fig. 20 D is the statistical result of GAP43 expression level; Fig. 20 B is the staining image of angiogenesis markers (VEGF and CD31) on day 7. Fig. 20 E is the statistical result of VEGF expression level, Fig. 20 F is the statistical result of CD31 expression level.
[0049] Fig.21 These are the hematoxylin-eosin (H&E) staining results of the heart, liver, spleen, lung and kidney tissues of the rats in each group after treatment for 14 days in Example 9.
[0050] Figure 1-21 The error bars represent mean ± standard deviation, *p<0.05 DETAILED DESCRIPTION
[0051] The technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments.
[0052] Unless otherwise specified, the experimental methods used in the following examples are all conventional experimental methods. Reagents and materials used in the following examples: gelatin (GEL, Shanghai Aladdin Industrial Co., Ltd., China), polycaprolactone (PCL, Sigma-Aldrich, USA), zinc nitrate hexahydrate (Zn(NO3).6H2O, Guangdong Xilong Science Co., Ltd.), 3,5-dihydroxybenzoic acid (3,5-DBHA, 97%, Shanghai MacLean Company), 2,2,2-trifluoroethanol (TFEA, 99.5%, Shanghai Aladdin Industrial Co., Ltd.), Cell Counting Kit-8 (cck8, New Saimei Biotechnology Co., Ltd.), 4% formaldehyde fixative solution (Solebao), crystal violet staining solution (Biyuntian, China), DAPI (Biyuntian, China), phosphate buffered saline (PBS, pH 7.4, Solebao), fetal bovine serum (FBS), DMEM medium (Gibico, DMEM), trypsin-EDTA and penicillin-streptomycin (Solebao), 24-well Transwell (8 μm pore size, Corning, 3422), Matrigel Matrix was purchased from Corning (New York, USA), and DPPH free radical scavenging ability test kit (Solarbio).
[0053] Example 1 Preparation and characterization of physical and chemical properties of electrospun fiber membrane
[0054] 1.1 Preparation of electrospinning fiber membrane: 10% (m / v) polycaprolactone (PCL) solution was prepared using TFEA, and different concentrations of zinc nitrate hexahydrate were added and stirred until uniform; then, 20% (m / v) gelatin aqueous solution was prepared and mixed with equal volumes of PCL / zinc nitrate solution to form an electrospinning solution, so that the final concentration of zinc nitrate hexahydrate in the electrospinning solution was 0, 2, 4, 6, 8 and 10 mg / mL; the electrospinning solution was electrospun at 20 kV high voltage, the injection speed was set to 1.0 mL / h, the distance between the collector and the needle tip was 120 mm, and the collector speed was 200 rpm to obtain a nanofiber membrane.
[0055] The nanofiber membrane was immersed in a 4% (m / v) 3,5-DHBA ligand solution, taken out after self-organization reaction at 37°C for 1 h, and dried at 37°C for 3 h to obtain the neuralization-promoting electrospun fiber membrane, which were named PG, PGZ2, PGZ4, PGZ6, PGZ8 and PGZ10 according to the different concentrations of zinc nitrate hexahydrate in the electrospinning solution.
[0056] 1.2 Screening of electrospun fiber membranes: PGZ4 samples were prepared according to the preparation process described in 1.1, except that the self-assembly reaction parameters were immersion at 37 °C for 0.5, 1, and 2 h. PGZ4 samples with different self-assembly reaction times were obtained, and the morphology of each fiber was observed using a scanning electron microscope (SEM, SU8010, Japan). Figure 2 As shown: an obvious coating layer or particle structure can be observed on the surface of the PGZ4 sample immersed for 1 h, while it is not obvious on the 3,5-DHBA / Zn-MOF particles in the immersion groups of 0.5 and 2 h, indicating that too long a self-assembly reaction time will cause the coating layer or particle structure to degrade.
[0057] The PGZ4 samples were prepared according to the preparation process described in 1.1, except that the drying treatment was carried out at 37°C for 1, 3, 6, 12 and 24 h, respectively. Figure 3 As shown in the figure, a dry electrospun membrane sample can be obtained after 3 h of treatment, but as the drying time increases, the sample shrinks and its brittleness increases significantly.
[0058] The PGZ4 samples were prepared according to the preparation process described in 1.1, except that the drying treatment was carried out at 37, 45 and 55°C for 3 h, respectively. Figure 4 As shown, the surface of the electrospun membrane in the 37°C group was relatively flat, while in the 45°C and 55°C groups, wrinkles appeared on the sample surface to varying degrees.
[0059] The cell compatibility of the different electrospun membranes in 1.1 was evaluated using the CCK8 assay. The results are shown in Figure 5Compared with the PG control group, 2+ The activity of Schwann cells was comparable in the PGZ2 and PGZ4 groups at high doses. 2+ In the PGZ6, PGZ8 and PGZ10 groups with different doses, the activity of Schwann cells gradually decreased, showing PGZ6>PGZ8>PGZ10. Therefore, the PG, PGZ2, PGZ4 and PGZ6 samples in 1.1 were selected as the experimental samples of the present invention to carry out the related experiments of 1.3 and Examples 2-8.
[0060] 1.3 Characterization of the physical and chemical properties of electrospun fiber membranes: The morphology of the experimental sample fibers was observed using a scanning electron microscope (SEM, SU8010, Japan). 150 fibers were randomly selected and the diameter of the nanofibers was measured using Image J. The SEM images of each group of electrospun membranes are shown in Figure 2. Figure 6 As shown in the figure: PG fibers are evenly distributed and have a relatively smooth surface, while the surface of PGZ electrospun fibers has a rough particle structure and is unevenly distributed. Image J measurement results show that compared with PG membranes, the fiber diameters of the PGZ series electrospun membranes are slightly increased: the diameters of PG, PGZ2, PGZ4, and PGZ6 fibers are 387.41±92.98 nm, 409.31±173.20 nm, 437.51±186.26 nm, and 419.43±129.97 nm, respectively.
[0061] Statistical analysis of the SEM image results showed that the particle size of 3,5-DHBA / Zn-MOF particles loaded on PGZ2, PGZ4 and PGZ6 electrospun membranes was 100-200nm.
[0062] The distribution of Zn element on the surface of the experimental samples was analyzed by X-ray energy dispersive spectrometer (Phenom Pharos, Netherlands). The EDS results are shown in Figure 6 As shown, the contents of zinc in the electrospun membranes of the PG, PGZ2, PGZ4, and PGZ6 groups were 0%, 0.48±0.07 wt%, 0.56±0.06 wt%, and 0.66±0.08 wt%, respectively, confirming that zinc ions had been successfully incorporated into the electrospun membranes.
[0063] The crystal structure of the experimental samples was observed using an X-ray diffractometer (Rigaku SmartLab SE, Japan). The XRD analysis results are shown in Figure 7 A and Figure 8 As shown, with the Zn 2+As the concentration increases, the diffraction peaks (10.3° and 10.7°) of MOF in the PGZ film become more and more obvious, indicating that as the zinc concentration increases, more MOF particles are formed. However, the amplitude of the diffraction peak is relatively small, which indicates that DBHA and Zn may not be completely polymerized and only partially form a crystal structure. The crystallinity of 3,5-DHBA / Zn-MOF particles was calculated using the Williamson-Hall diagram of the Origin software. The crystallinity of the PGZ2, PGZ4, and PGZ6 groups was 57.6%, 64.0%, and 55.6%, respectively.
[0064] The chemical composition of different experimental samples was evaluated using Fourier transform infrared spectrometer (FTIR, Nicolet iS20, Thermo Fisher Scientific, USA). Figure 7 As shown in B, the absorption peaks at 2942-2866 cm⁻¹ are the stretching vibration peaks of CH, 1724 cm⁻¹ is the stretching vibration peak of ester group C=O, 1639 cm⁻¹ is the stretching vibration peak of carboxyl group C=O, 1544 cm⁻¹ is the benzene ring skeleton vibration peak, and 1005 cm⁻¹ is the stretching vibration peak of phenol CO.
[0065] The surface hydrophilicity was measured by a contact angle meter (JY-82C, Chengde Dingsheng). The water contact angle values of each electrospun membrane were approximately 46.09°, 28.89°, 48.49°, and 46.26°, respectively, showing good hydrophilicity.
[0066] The above results collectively confirmed that the PGZ electrospun membrane had been successfully prepared.
[0067] Example 2 Mechanical properties of PGZ electrospun membrane
[0068] The mechanical properties of the nanofiber membranes were tested using a universal material testing machine (INSTRON 5982 / 8872 / CMT4104 / RGM-6300, USA). The experimental samples were cut into squares of standard size (3 cm × 3 cm × 0.2 cm) and fixed on the fixture. The tensile test was carried out at a speed of 10 mm / min under the action of a 100 N load cell (BAB-20MT, Transcell Technology, USA). The stress-strain curves of the four groups of membranes all followed Hooke's law in the early stage. The Young's modulus of the PG, PGZ2, PGZ4 and PGZ6 electrospun membranes were 46.71 MPa, 120.33 MPa, 142.07 MPa and 99.73 MPa, respectively; the maximum tensile strength (UTS) was 2.76 KPa, 5.81 KPa, 6.40 KPa and 6.14 KPa, respectively. The results show that the formation of 3,5-DHBA / Zn-MOF particles significantly improves the Young's modulus and maximum tensile strength of the PGZ film.
[0069] Example 3 In vitro degradation of electrospun membranes and 3,5-DHBA / Zn 2+ release
[0070] 3.1 In vitro degradation rate of PGZ electrospun membrane: The experimental samples were immersed in PBS solution and incubated at 37 °C. After different time points (0, 1, 3, 5, 7, 14, 21 and 35 days), the samples were taken out, wiped dry of excess water, and weighed (W1), and compared with their original weight (W0).
[0071] The calculation formula of degradation rate is: degradation rate = [(W0 - W1) / W0] × 100%.
[0072] The results of in vitro degradation experiments of PGZ electrospun membranes are shown in Fig. 9 As shown in A, the four groups of samples degraded significantly in the first week, and the degradation rate of each group of samples gradually decreased in the next four weeks. On the 35th day, the weight loss rate of the PG group was about 70%, while the weight loss rates of PGZ2, PGZ4 and PGZ6 samples were lower than that of the PG group, about 65%.
[0073] 3.2 Drug release characteristics of PGZ electrospun membrane: The experimental samples were immersed in 5 mL of PBS solution and incubated at 37 °C. The extracts were collected for testing at 1, 3, 5, 10, 14 and 21 days to evaluate the drug release characteristics. The absorbance at 302 nm was measured by spectrophotometry, and the drug release amount and cumulative release amount at each time point were calculated based on the DBHA standard curve equation. At the same time, an inductively coupled plasma optical emission spectrometer (ICP-OES, Thermo Fisher, USA) was used to monitor the zinc ion content in the solution and calculate the cumulative release amount.
[0074] The drug release results were as follows Fig. 9 As shown in B and 9C, the PGZ4 group had more 3,5-DHBA and Zn compared with PGZ2 and PGZ6. 2+ The three groups of 3,5-DHBA released faster in the first five days, but released slowly in the later period. On the fifth day, the release of 3,5-DHBA in the PGZ2, PGZ4 and PGZ6 groups was 0.86±0.06 mg / mL, 1.16±0.01 mg / mL and 0.98±0.03 mg / mL, respectively, and on the 21st day, it was 1.19±0.05 mg / mL, 1.53±0.02 mg / mL and 1.23±0.05 mg / mL, respectively. Fig. 9 C, Zn 2+ The release curves also showed similar release behaviors, but the release rate was faster in the first 10 days and then slowed down. 2+ The release amounts of Zn in the PGZ6 group on the 21st day were 17.15±0.67 μg / mL, 47.38±2.14 μg / mL, and 15.84±0.62 μg / mL, respectively, while at the 21st day they were 91.25±1.10 μg / mL, 128.90±2.48 μg / mL, and 117.17±3.31 μg / mL, respectively. 2+ The release amount exceeded that of PGZ2, but the early Zn 2+ The release amount is lower than that of PGZ2.
[0075] Combined with the XRD results ( Figure 7 A and Figure 8 ), in the PGZ2 group, due to the initial addition of Zn 2+ When the nanofiber membrane contacts with the DHBA soaking solution, it cannot form sufficient coordination reaction, resulting in a small amount of MOF and low crystallinity. 2+ The addition amount of DHBA and Zn was moderate, so MOF with appropriate content and crystallinity was formed, showing the application of DHBA and Zn in the dressing field. 2+Release behavior; In the PGZ6 group, due to the initial addition of Zn 2+ Although the DHBA diffusion rate and other factors make it difficult to form a perfect MOF structure inside the fiber, the Zn 2+ It can be fully combined with DHBA to form MOF particles with high crystallinity. This distribution of gradually decreasing crystallinity from the outer layer to the inner layer (the overall performance is low crystallinity) makes this group of Zn 2+ The early release rate is slow, while the later release rate gradually accelerates. In addition, since the MOF on the surface of PGZ2 and PGZ4 fibers is not completely crystallized, a large number of uncoordinated chemical groups such as carboxyl and phenolic hydroxyl groups remain.
[0076] Example 4 In vitro coagulation, swelling, hemolysis and antioxidant properties of PGZ electrospun membranes
[0077] 4.1 In vitro coagulation performance of PGZ electrospun membrane: The coagulation performance of the electrospun membrane in vitro was evaluated using a coagulation experiment. The experimental samples were placed in a culture dish and preheated in a 37°C incubator for 6 min. 100 μL of fresh rat whole blood was added to the surface of the electrospun membrane. After incubation at 37°C for 5 min, 1 mL of deionized water was added to remove red blood cells that were not absorbed by the electrospun membrane. The electrospun membrane containing the blood clot was collected and placed in a 2 mL centrifuge tube for ultrasonic treatment. After further centrifugation at 3000 rpm, the supernatant was collected and the OD value was measured at 545 nm. The relative coagulation amount of each group of nanofiber membranes was calculated according to the following formula: Relative blood clotting (%) = ODn / ODa × 100﹪, where ODn and ODa are the OD values of each experimental group and control group at 545 nm, respectively.
[0078] The sample absorbs red blood cells. Fig.10 As shown in A, compared with the other two groups of materials, the coagulation area on the surface of PGZ2 and PGZ4 samples is significantly larger. The relative coagulation amounts of PGZ2, PGZ4 and PGZ6 groups are approximately 394.35%, 395.69% and 165.86%, respectively. This shows that the coagulation function of PGZ electrospun membrane is better than that of PG membrane, among which PGZ2 and PGZ4 membranes have the best coagulation function. It is confirmed that there are a large number of uncoordinated carboxyl, phenolic hydroxyl and other chemical groups on the surface of PGZ2 and PGZ4 fibers. When these chemical groups come into contact with blood, they quickly trigger the coagulation cascade reaction and eventually form more blood clots. Relatively speaking, the highly crystalline MOF on the surface of PGZ6 fibers has fewer residual uncoordinated chemical bonds, so the relative coagulation amount is less.
[0079] 4.2 Swelling properties of PGZ electrospun membrane: The experimental samples were cut into 1.5 × 1.5 cm discs, immersed in a 37°C incubator for drying, and weighed (M0). Subsequently, an appropriate amount of PBS solution was added and soaked for 24 h, and the wet weight (M1) was measured. The swelling rate was calculated according to the following formula: Swelling rate = [(M1 - M0) / M0] × 100%.
[0080] The swelling rate calculation results are as follows: Fig.10 As shown in Figure B, the swelling rate of PGZ electrospun membrane is significantly better than that of PG membrane. The swelling rates of PG, PGZ2, PGZ4 and PGZ6 are 1.8%, 94.2%, 97.5% and 56.5%, respectively. This shows that PGZ membrane has good water absorption and is helpful for the absorption of wound exudate.
[0081] 4.3 Hemolytic performance of PGZ electrospun membrane: The blood compatibility of the electrospun membrane was evaluated using a blood hemolysis experiment. Take 5 mL of fresh rat whole blood and centrifuge at 2000 rpm for 15 min to obtain a red blood cell (RBCs) precipitate. Dilute the red blood cell precipitate with normal saline to prepare an RBCs suspension. Take 1 mL of the suspension and immerse the experimental sample with a size of 15 mm × 15 mm × 2 mm in a centrifuge tube and incubate at 37°C for 2 h. After incubation, centrifuge for 10 min, carefully pipette the supernatant into a 96-well plate, and measure its OD value at 540 nm. The experiment set the DI water group as the positive control and the normal saline group as the negative control, and calculated the blood compatibility hemolysis rate according to the following formula:
[0082] Hemolysis ratio(﹪) = (AS−AT) / (AC−AT)×100﹪.
[0083] In the formula, AS is the OD value of the sample, AC and AT are the OD values of the positive control and negative control groups, respectively.
[0084] Hemolysis test results Fig.10 As shown in Figures C and 10E, the supernatants of the four groups of electrospun membranes were clear and transparent, and the hemolysis rates were 0.66% (PG), 0.69% (PG2), 2.12% (PG4), and 2.11% (PG6), respectively. Materials with a hemolysis rate below 5% have good blood compatibility and meet the standards for use in clinical applications.
[0085] 4.4 Antioxidant properties of PGZ electrospun membrane: The antioxidant properties of the fiber membrane were evaluated using the 1,1-diphenyl-2-picrylhydrazide (DPPH) free radical scavenging method. Take 50 mg of the electrospun membrane, soak it in 1 mL of the DPPH kit extract, and incubate it in a 40°C thermostat in the dark for 2 h. Subsequently, centrifuge it at 10,000 rpm at room temperature for 10 min, take the supernatant and immerse it on ice for later use. According to the instructions of the kit, the blank group, control group, assay group and positive group were configured. After being immersed in room temperature for 30 min in the dark, the absorbance was measured at 515 nm, which were recorded as A blank, A assay and A control, respectively. The free radical scavenging rate of the sample is calculated as:
[0086] DPPH free radical scavenging rate D% = [[A blank - (A test - A control)] ÷ A blank] × 100%.
[0087] like Fig.10 As shown in Figures 10D and 10F, the DPPH scavenging rates of PG, PGZ2, PGZ4, and PGZ6 electrospun membranes were 13.22%, 75.11%, 74.65%, and 72.13%, respectively, indicating that the PGZ electrospun membrane had excellent antioxidant activity.
[0088] The above results prove that compared with PG electrospun membrane, the 3,5-DHBA / Zn-MOF particles with rigid structure make the PGZ electrospun membrane have excellent antioxidant activity; among them, the PGZ2 and PGZ4 groups also showed excellent in vitro coagulation performance, high water absorption and low hemolysis rate, and have good prospects for dressing development.
[0089] Example 5 Preparation of material extract and Schwann cell (SCs) conditioned medium
[0090] A medium containing 33 mM sugar concentration was used to simulate the high-sugar microenvironment of diabetes. The experimental samples were cut into 1.5 × 1.5 cm discs, sterilized under ultraviolet light for 12 h, immersed in 1 mL (1 disc / 1 mL) high-glucose DMEM medium without FBS, and immersed in an incubator at 37°C and 5% CO2 for 72 h. The supernatant was collected by centrifugation as the material extract.
[0091] In addition, Schwann cells (purchased from ATCC Biological Standard Resource Center, USA) were cultured at 2×10 4 The cells were inoculated at a density of 100 cells / well in the extract of the above materials, and the culture supernatant was collected after incubation for 2 days as SCs conditioned medium.
[0092] Example 6 Effect of PGZ electrospun membrane on the biological behavior of nerve-related cells
[0093] 6.1 Effects of PGZ electrospun membranes on the biological behavior of Schwann cells (SCs)
[0094] 6.1.1 Morphology of Schwann cells: Schwann cells were inoculated in the material extract and incubated for 48 h, fixed with 4% paraformaldehyde (Solebo, China), and the cell membrane was permeabilized with Triton X-100. Subsequently, rhodamine-labeled phalloidin (Biosharp, China) was added and incubated at 4°C in the dark for 1 h. After changing to DAPI staining and incubating at room temperature in the dark for 5 min, the cell morphology was observed by inverted fluorescence microscopy.
[0095] The cell morphology results are as follows Fig.11 As shown in A, after being cultured in the material extract, the Schwann cells in each group had good spreading, and the cells in the PGZ group (especially PGZ6 and PGZ4) had more pseudopodia.
[0096] 6.1.2 Schwann cell activity and proliferation: First, the CCK8 kit (Biyuntian, China) was used to detect the cell activity of Schwann cells. 4 The cells were inoculated at a density of 100 / well in the extracts of each group of materials. After incubation for 2 and 5 days, the culture medium was replaced with a pre-prepared 10% CCK-8 solution. After further incubation for 2 hours, the absorbance was measured at 450 nm using an automatic multifunctional microplate reader (Bio-Rad680, Thermo, USA). The results are shown in Figure 2. Fig.11 As shown in B, the PGZ6 material loaded with a large amount of MOF inhibited the activity of Schwann cells, while there was no difference in the cell activity of the other three groups.
[0097] The proliferation capacity of Schwann cells was evaluated using an EDU kit (Biyuntian, China). Schwann cells were incubated in the material extract for 2 days, replaced with 10 μM EdU solution for 2 h, and then fixed with 4% paraformaldehyde, permeabilized with 0.2% Triton X-100, and stained with Hoechst 33342 (5 μg / mL). Finally, the cells were observed under a fluorescent inverted microscope (Leica, Germany), and the cell proliferation rate was calculated using ImageJ software. The EDU results are shown in Figure 2. Fig.11 As shown in A and 11C, it is confirmed that as the amount of MOF in the electrospun membrane increases, the proliferation rate of Schwann cells in the extract of the corresponding material gradually decreases (PGZ6 <PGZ4<PGZ2<PGZ)。
[0098] 6.1.3 Schwann cell migration: The Transwell system was used to evaluate the migration ability of SCs in the material extract. 4SCs / well were seeded in the upper chamber of a 24-well Transwell (3422, Corning, USA), and material extract containing 20% FBS was added to the lower chamber. After incubation for 48 h, the filter was fixed with 4% paraformaldehyde and stained with crystal violet. After scraping off the non-migrated cells in the upper chamber, the migrated cells were observed and counted under an optical microscope (Leica, Germany). Fig.11 As shown in A and 11D, it can be seen that the number of migrating cells in the PGZ2, PGZ4, and PGZ6 groups was significantly higher than that in the PG group, especially in the PGZ4 group.
[0099] 6.1.4 Schwann cell cycle: SCs were inoculated in the sample high-glucose extract and cultured for 48 h. According to the instructions of the Bio-Tech kit, cells were collected with trypsin and fixed with 70% ethanol overnight. Subsequently, they were stained with propidium iodide and incubated at 37°C in the dark for 30 min. The cell cycle distribution was detected using a flow cytometer (Agilent, USA) at an excitation wavelength of 488 nm. It was found that more cells in the PGZ group were retained in the G1 phase, which were approximately: 64.49±2.18% (PG), 67.17+0.44% (PGZ2), 71.78±1.75% (PGZ4), and 68.64+1.31% (PGZ6).
[0100] 6.1.5 ROS expression in Schwann cells: To evaluate the ability of experimental samples to scavenge intracellular ROS (reactive oxygen species), Schwann cells co-cultured with the sample high-glucose extract for 48 h were labeled with DCFH-DA dye, and the nuclei were stained with DAPI. The staining results are shown in Fig.11 As shown in A. ImageJ software was used to quantify the ROS fluorescence intensity. Fig.11 As shown in Figure E, the results show that compared with the PG electrospun membrane, the fluorescence intensity of the electrospun membranes in the PGZ2, PGZ4, and PGZ6 groups was significantly weakened, indicating that the PGZ membrane can significantly remove intracellular ROS. This further confirms that the PGZ electrospun membrane has significant antioxidant activity.
[0101] 6.2 Effects of PGZ electrospun membrane on the biological behavior of PC12
[0102] 6.2.1 Morphology of PC12 cells: PC12 cells (purchased from ATCC Biological Standard Resource Center, USA) were cultured at 0.5×10 4 The cells were inoculated in SCs conditioned medium at a density of 100 cells / well. After culturing for 48 h, the cell morphology of each group of cells was detected (the specific method is the same as 6.1.1). The results are as follows: Fig.12 As shown in A. Image J software was used to quantify the percentage of cells with neurites and the length of neurites. Fig.12As shown in B and 12C , the percentages of neurite cells (cells with neurite lengths exceeding 10 μm were designated as neurite cells) in each group were approximately 20%, 33.6%, 55%, and 21.6%, respectively, and the neurite lengths were approximately 37.66 μm, 54.66 μm, 79.33 μm, and 40 μm, respectively.
[0103] 6.2.2 Neural differentiation trend of PC12 cells: PC12 cells were cultured at 2×10 4 The cells were seeded at a density of 100 cells / well in SCs conditioned medium. After 48 h of culture, total RNA was extracted using a total RNA kit (Vazyme, China), and cDNA was reverse transcribed using a PrimeScriptTM RT-qPCR kit (TAKARA). The expression of nerve regeneration-related genes TUJ-1, SYN, and GAP-43 in PC12 cells was evaluated by RT-qPCR using the Roche LightCycler 480 system. The primer sequences of the related genes are shown in Table 1.
[0104] Table 1 Primer sequences
[0105]
[0106] The expression levels of TUJ-1, SYN, and GAP-43 axon-related genes in different groups are as follows Fig.12 They were expressed at the highest levels in the PGZ4 group as shown in D. These results indicate that more PC12 cells in the PGZ4 group showed a tendency toward neurogenic differentiation compared with the PG group.
[0107] 6.2.3 Cell viability of PC12 cells: Cell viability assay (CCK-8) was performed on PC12 cells cultured in SCs-conditioned medium for 2 and 5 days. The results are shown in Table 1. Fig.13 There is no significant difference as shown in A, which indicates that the PGZ electrospun membrane has good compatibility with PC12 cells.
[0108] Example 7 Effect of PGZ electrospun membrane on biological behavior of vascular endothelial cells
[0109] 7.1 Effect of PGZ electrospun membrane on VECs cell activity, cell migration, and ROS expression: Vascular endothelial cells (VECs) were purchased from the ATCC Biological Standards Resource Center in the United States. VECs were cultured at 2×10 4 After being inoculated at a density of 100 cells / well in the material extract or SCs conditioned medium, the cell activity (cultured for 1 and 3 days, the specific method is the same as 6.1.2), cell migration (cultured for 48 hours, the specific method is the same as 6.1.3), and ROS expression (cultured for 48 hours, the specific method is the same as 6.1.5) of each group of cells were detected.
[0110] The results of the VECs activity experiment are shown in Figures 13B and 13C. There was no significant difference in the cell activity among the groups, indicating that the PGZ electrospun membrane has good compatibility with vascular endothelial cells.
[0111] The ROS experimental image results are as follows Fig.14 As shown in A and 14B, after DCFH-DA was used to label vascular endothelial cells, the ROS fluorescence of the PGZ group in both culture media was significantly weakened, indicating that the PGZ group was able to significantly clear ROS in endothelial cells, thereby protecting them from oxidative stress in a high glucose environment.
[0112] In the VECs migration experiment, endothelial cells cultured in the material extract were Fig.14 As shown in A, the number of migrating cells in the PGZ2 and PGZ4 groups was significantly greater than that in the PG group. Fig.14 As shown in B, the trend in SCs conditioned medium is more significant: compared with the culture in material extract, the number of endothelial migratory cells under SCs conditioned culture is greater, and the effect of PGZ2 and PGZ4 groups is the most prominent.
[0113] 7.2 Effect of PGZ electrospun membrane on VECs tube formation: VECs were seeded in a cell culture plate covered with Matrigel (Corning, USA) and incubated in material extract or SCs conditioned medium for 2 and 6 h. The formed tubular structures were photographed using an inverted microscope (Leica). Fig.14 A, 14B and 15A, and then use Image J software to count the total tube length and number of nodes, where the number of nodes at 6 hours is as follows Fig.14 C and 14E, the total branch length is Fig.14 As shown in D and 14F, the PGZ group showed significant advantages in the tube formation experiment; further comparison of the endothelial cell tube formation results between the PGZ4 and PG groups was as follows Fig.15 As shown in B and 15C, the endothelial cells in the PGZ4 group had formed tubular structures in the SCs-conditioned medium for 2 hours, and the structures were more obvious after 6 hours. The SCs-conditioned medium promoted angiogenesis more effectively.
[0114] Example 8 Effect of PGZ electrospun membrane on biological behavior of fibroblasts
[0115] Skin fibroblasts (RS1) were purchased from ATCC Biological Standards Resource Center, USA. RS1 cells were cultured at 2×10 4 After being inoculated at a density of 100 cells / well in the material extract or SCs conditioned medium, the cell activity (cultured for 1 and 3 days, the specific method is the same as 6.1.2), cell migration (cultured for 48 hours, the specific method is the same as 6.1.3), and ROS expression (cultured for 2 days, the specific method is the same as 6.1.5) of each group of cells were detected.
[0116] The statistical results of RS1 cell activity are as follows Fig.13 As shown in D and 13E, there was no significant difference in the cell activity among the groups, indicating that the PGZ electrospun membrane had good compatibility with fibroblasts.
[0117] ROS experimental images and statistical results are shown in Fig.16 As shown in A, 16B, and 16D, after RS1 cells were labeled with DCFH-DA, it was found that the ROS fluorescence of the PGZ group was significantly weakened under both culture conditions, indicating that the PGZ group was able to significantly clear ROS in RS1, thereby protecting it from oxidative stress under a high glucose environment.
[0118] The images and statistical results of RS1 migration experiment in material extract are as follows: Fig.16 As shown in A, 16C, and 16E, the number of migrating cells in the PGZ2 and PGZ4 groups was greater than that in the PG group. The results of the RS1 migration experiment in SCs conditioned medium are shown in Fig.16 As shown in Figure E, the trend is similar to that in the material extract, and this phenomenon is more obvious, and the migration numbers of PGZ2 and PGZ4 are particularly significant.
[0119] Example 9 Wound repair in diabetic rats
[0120] The experimental results of Examples 2-8 showed that the PGZ4 sample had better biological functions in the field of dressing applications. The PGZ4 electrospun membrane was selected as a representative for in vivo experiments to verify the effect of the PGZ electrospun membrane in accelerating diabetic wound healing in vivo. Non-diabetic rats (Normal group) were used as positive controls, untreated diabetes group (DM) and PG group (DM / PG) were used as controls, and the PGZ4 group (DM / PGZ4) was used as the experimental group.
[0121] like Fig.17The process shown in A was used to establish a rat back wound model and evaluate the ability of electrospun membranes to promote wound healing. All animal procedures were approved by the Experimental Animal Ethics Committee of Ruian People's Hospital (Ethics Review Approval No. DWSY-2024-013). Fifty male Sprague-Dawley rats (6 weeks, 150-200 g) were selected and the diabetic model was established by intraperitoneal injection of streptozotocin (STZ, 60 mg / kg, Sigma). Blood glucose and body weight were monitored on days 0, 3, 7, and 14 after injection, and rats with random blood glucose levels exceeding 16.7 mmol / L and lasting for 2 weeks were diagnosed with diabetes. After successful modeling, the rats were randomly divided into the Normal group, DM group, DM / PG group, and DM / PGZ4 group for wound healing experiments. A full-thickness skin incision with a diameter of 1 cm was made on both sides of the back of each rat. The rats in the Normal and DM groups were not covered with materials, while the rats in the DM / PG and DM / PGZ4 groups were covered with PG and PGZ4 electrospun membranes, respectively. Wound photos were taken on days 0, 3, 7, and 14 after surgery, and the remaining wound area was calculated using Image J software. Rats were killed on days 3, 7, and 14, and wound tissues were collected and subjected to H&E staining, Masson staining, and immunohistochemical staining to evaluate wound healing. In addition, the heart, liver, spleen, lung, and kidney of the rats were collected and subjected to H&E staining to evaluate the biocompatibility of the fiber material in vivo.
[0122] Three weeks after STZ injection, H&E staining results showed that the pancreatic islet tissue in the pancreas of rats in the DM group was relatively atrophied compared with rats in the Normal group. The blood glucose and body weight of rats in the Normal and DM groups showed a significant upward and downward trend, respectively (*p<0.05); on the 14th day, the blood glucose and body weight of rats in the DM group were 27.02±1.48 mmol / L and 398.42±16.57 g, respectively, while those of rats in the Normal group were 6.10±0.71 mmol / L and 209.50±19.03 g. This indicates that the diabetic rat model was successfully established.
[0123] Postoperative wound photos and percentage of remaining wound area Fig.17 As shown in Figures B and 17C, after 3, 7, and 14 days of wound repair, the wound area of each group gradually decreased. Among them, the healing speed of the DM / PGZ4 group was significantly accelerated, approaching the healing speed of normal rats. The wound skin at each time period was further collected and evaluated by Masson staining to further verify the therapeutic effect of the PGZ4 electrospun membrane. H&E staining results and statistical data are shown in Fig.18As shown in A and 18B, compared with the DM and DM / PG groups, the Normal and DM / PGZ4 groups had more inflammatory cells at 3 days, while the inflammatory cells were significantly reduced at 7 and 14 days; while the early inflammation in the DM and DM / PG groups was delayed, and the late inflammation dissipated slowly. The Masson staining results and statistical results are shown in Fig.19 As shown in A and 19B, the collagen deposition rates in the Normal and DM / PGZ4 groups were significantly higher than those in the DM and DM / PG groups on days 3, 7, and 14 (*p<0.05). The above results indicate that PGZ4, as a wound dressing, can not only promote the dissipation of inflammation in diabetic wounds, but also significantly promote the deposition of collagen in diabetic wounds, thereby effectively promoting wound healing.
[0124] Immunohistochemical staining was performed on the skin wound tissue on the 7th day, and the expression levels of neural markers (NGF and GAP-43) and vascular markers (VEGF and CD31) were statistically analyzed. The results are as follows Fig. 20 As shown. Compared with the DM and DM / PG groups, the expression levels of neural indicators (NGF and GAP-43) and vascular indicators (VEGF and CD31) in the new tissue of the wound surface in the Normal and DM / PGZ4 groups were significantly upregulated (*p<0.05). Among them, the positive rates of GAP43 and CD31 in the DM / PGZ4 group were approximately 13.5 and 3 times that of the DM group, respectively. The expression levels of NGF, GAP-43 and CD31 proteins in the DM / PGZ4 group were also significantly higher than those in the Normal group (*p<0.05).
[0125] The heart, liver, spleen, lung, and kidney of rats in each group after 14 days of treatment were stained with hematoxylin-eosin (H&E). Fig.21 As shown, there was no significant difference in the morphological structure of organs in each group, indicating that the materials used were non-toxic to other organs of rats.
[0126] In summary, the PGZ4 group electrospun membrane has good biocompatibility and can effectively promote nerve and blood vessel regeneration, thereby accelerating the process of diabetic wound healing.
[0127] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A neuralization-promoting electrospun fiber membrane, characterized in that: The neuralization-promoting electrospun fiber membrane comprises a plurality of nanofibers loaded with 3,5-DHBA / Zn-MOF particles, wherein the 3,5-DHBA / Zn-MOF particles are composed of Zn 2+ and 3,5-DHBA self-assembled to form the neuralization-promoting electrospun fiber membrane 2+ The mass percentage is 0.48-0.66%.
2. The neuralization-promoting electrospun fiber membrane according to claim 1, characterized in that: The diameter of the nanofiber is 380-440 nm; the particle size of the 3,5-DHBA / Zn-MOF particles is 100-200 nm, and the crystallinity is 55.6%-64.0%.
3. A method for preparing a neuralization-promoting electrospun fiber membrane according to any one of claims 1 to 2, characterized in that: The preparation method comprises the following steps: Step (1): Preparation of Zn 2+ An electrospinning solution having a concentration of 0.44-1.32 mg / mL, and electrospinning the electrospinning solution to obtain a nanofiber membrane; Step (2): immersing the nanofiber membrane obtained in step (1) in a 3,5-DHBA ligand solution, taking it out after self-assembly reaction for 0.5-2 h, and drying it to obtain the neuralization-promoting electrospun fiber membrane.
4. The preparation method according to claim 3, characterized in that: The electrospinning solution in step (1) further comprises a biocompatible hydrophilic polymer, wherein the biocompatible polymer is selected from any one of polycaprolactone, lactide-caprolactone copolymer, sodium alginate, chitosan, gelatin or hyaluronic acid, or a combination of at least two thereof.
5. The preparation method according to claim 3, characterized in that: The electrospinning solution in step (1) is a gelatin / polycaprolactone electrospinning solution, and the nanofiber membrane is a gelatin / polycaprolactone nanofiber membrane.
6. The preparation method according to claim 3, characterized in that: The molar concentration of 3,5-DHBA in the 3,5-DHBA ligand solution of step (2) is not less than one-fourth of the molar concentration of Zn in the electrospinning solution of step (1). 2+ The molar concentration of .
7. The preparation method according to claim 6, characterized in that: The mass volume percentage concentration of the 3,5-DHBA ligand solution is 4%.
8. The preparation method according to claim 5, characterized in that: The drying parameters of step (2) are a drying temperature of 37° C. and a drying time of 3 h.
9. The preparation method according to claim 3, characterized in that: The electrospinning parameters are: loading voltage 15-20 kV high voltage, injection speed 0.2-1.0 mL / h, distance between collector and needle tip 100-120 mm, collector rotation speed 100-200 rpm.
10. The preparation method according to claim 3, characterized in that: Zn in step (1) 2+ Derived from any one of zinc nitrate hexahydrate, zinc acetate, and zinc chloride.
Citation Information
Patent Citations
Raloxifene modified MOF coating mediated local anti-osteoporosis metal base material implant material and preparation method thereof
CN112546300A
Application of DHB-Zn MOF nano material as matrix in mass spectrometry detection
CN114720550A